Human placental oxygenation in late gestation: experimental and theoretical approaches. (25th February 2018) - Nye, Gareth A.; Ingram, Emma; Johnstone, Edward D.; Jensen, Oliver E.; Schneider, Henning; Lewis, Rohan M.; Chernyavsky, Igor L.; Brownbill, Paul
Abstract: The placenta is crucial for life. It is an ephemeral but complex organ acting as the barrier interface between maternal and fetal circulations, providing exchange of gases, nutrients, hormones, waste products and immunoglobulins. Many gaps exist in our understanding of the detailed placental structure and function, particularly in relation to oxygen handling and transfer in healthy and pathological states in utero . Measurements to understand oxygen transfer in vivo in the human are limited, with no general agreement on the most appropriate methods. An invasive method for measuring partial pressure of oxygen in the intervillous space through needle electrode insertion at the time of Caesarean sections has been reported. This allows for direct measurements in vivo whilst maintaining near normal placental conditions; however, there are practical and ethical implications in using this method for determination of placental oxygenation. Furthermore, oxygen levels are likely to be highly heterogeneous within the placenta. Emerging non‐invasive techniques, such as MRI, and ex vivo research are capable of enhancing and improving current imaging methodology for placental villous structure and increase the precision of oxygen measurement within placental compartments. These techniques, in combination with mathematical modelling, have stimulated novel cross‐disciplinary approaches that could advance our understanding of placental oxygenation and its metabolism in normal and pathological pregnancies, improving clinical treatment options and ultimately outcomes for the patient. Abstract : There are a range of techniques to assess structure and function in the placenta. These techniques vary widely in resolution and accuracy in particular when assessing a crucial placental function, measuring oxygen levels. Very few techniques can study both structure and function to any high detail and so mathematical modeling has bridged the gap. However, the strength of the model relies entirely on the strength of the data gained from experimental procedures.